Laparoscopic Sleeve Gastrectomy versus Laparoscopic Banded Sleeve Gastrectomy: First Prospective Pilot Randomized Study. (10th April 2016) - Tognoni, Valeria; Benavoli, Domenico; Bianciardi, Emanuela; Perrone, Federico; Ippoliti, Simona; Gaspari, Achille; Gentileschi, Paolo
Abstract : Introduction . The placement of ring or band around the gastric tube might prevent the dilation after Laparoscopic Sleeve Gastrectomy (LSG). We describe the first randomized study comparing LSG and Laparoscopic Banded Sleeve Gastrectomy (LBSG). Material and Method . Fifty obese patients were enrolled in the study between January 2014 and January 2015. We analysed differences in operative time, complication rate, mortality, and BMI between the two groups over a period of 12 months. Results . Twenty-five patients received LSG (group A) and 25 LBSG (group B). The mean preoperative BMI was47.3 ± 6.58  kg/m 2 and44.95 ± 5.85  kg/m 2, respectively, in the two groups. There was no statistical relevant difference in operative time. No intraoperative complications occurred. Mean BMI registered after 3, 6, and 12 months in groups A and B, respectively, were37.86 ± 5.72  kg/m 2 and37.58 ± 6.21  kg/m 2 (p = 0.869 ), 33.64 ± 6.08  kg/m 2 and32.03 ± 5.24  kg/m 2 (p = 0.325 ), and29.72 ± 4.40  kg/m 2 and27.42 ± 4.47  kg/m 2 (p = 0.186 ); no statistical relevant difference was registered between the two groups. Conclusion . LBSG is a safe and feasible procedure. The time required for the device positioning did not influence significantly the surgical time. The results of bodyweight loss did not document any statistically significant differences among the two groups, even though LBSG group showed a mean BMI slightly lower than that of the control group.